Mechanical Characteristics of Organic Waste-Based Biodegradable Plastics with Variations in Cellulose Concentration and Synthesis Temperature - Cahyaningrum, Wahyu; Jonuarti, Riri; Gusnedi, -; Jhora, Fadhila Ulfa (PILLAR OF PHYSICS, 2024)
Biodegradable plastic is an innovative plastic material that is environmentally friendly because it has the property of being easily decomposed naturally by the activity of microorganisms.   Biodegradable plastics are generally made from starch and cellulose which are natural polymer materials that are easily decomposed in nature. Some organic wastes contain a lot of starch and cellulose, one of which is cassava peel and corn cob waste. In this study, starch from cassava peels was used as raw material in the manufacture of biodegradable plastics and cellulose from corn cobs which functioned as filler. The purpose of this study are to determine the effect of corn cob cellulose concentration and synthesis temperature on the mechanical properties and biodegradability of biodegradable plastics. In this study, the method used to make biodegradable plastic is by using the material mixing method. There are two treatment factors, namely variations in corn cob cellulose concentration of 0%, 1%, and 2% and synthesis temperature with variations of 70˚C, 80˚C, and 90˚C. The results showed the best characteristics for the tensile strength test at the addition of 2% of cellulose concentration and 90˚C synthesis temperature of 2.31 MPa. While the best elongation value is at 0% cellulose concentration and 90˚C synthesis temperature of 21%. The best biodegradation results were obtained from the addition of a cellulose concentration of 2% and synthesis temperature of 70˚C which decomposed perfectly in the soil for 8 days